Auditory Abilities after Cochlear Implantation in Adults with Unilateral Deafness: A Pilot Study - Firszt, Jill B. (2012)
OBJECTIVE: This pilot study examined speech recognition, localization, temporal and spectral discrimination and subjective reports of cochlear implant (CI) recipients with unilateral deafness. STUDY DESIGN: Three adult males with short-term unilateral deafness (< 5 years) participated. All had sudden onset of severe to profound hearing loss in one ear, which then received a CI, and normal or near normal hearing in the other ear. Speech recognition in quiet and noise, localization, discrimination of temporal and spectral cues and a subjective questionnaire were obtained over several days. Listening conditions were CI, normal hearing (NH) ear, and bilaterally (CI and NH). RESULTS: All participants had open-set speech recognition and excellent audibility (250–6000 Hz) with the CI. Localization improved bilaterally compared to the NH ear alone. Word recognition in noise was significantly better bilaterally than with the NH ear for two participants. Sentence recognition in various noise conditions did not show significant bilateral improvement; however, the CI did not hinder performance in noise even when noise was toward the CI side. The addition of the CI improved temporal difference discrimination for two participants and spectral difference discrimination for all participants. Participants wore the CI full time and subjective reports were positive. CONCLUSION: Overall, the CI recipients with unilateral deafness obtained open-set speech recognition, improved localization, improved word recognition in noise, and improved perception of their ability to hear in everyday life. A larger study is warranted to further quantify the benefits and limitations of cochlear implantation in individuals with unilateral deafness.